Chaotically encoded particle swarm optimization algorithm and its applications - Alatas, Bilal; Akin, Erhan (Pergamon-Elsevier Science Ltd, 2009)
This paper proposes a novel particle swarm optimization (PSO) algorithm, chaotically encoded particle swarm optimization algorithm (CENPSOA), based on the notion of chaos numbers that have been recently proposed for a novel meaning to numbers. In this paper, various chaos arithmetic and evaluation measures that can be used in CENPSOA have been described. Furthermore, CENPSOA has been designed to be effectively utilized in data mining applications. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Systems; Numbers